Developing “MEMANNAH” Digital Site on Prophet Muhammad and Medina’s Economy for Grade 5 PAI Learning - Mahmudah, Dwi Risa; Rizka, Fasya Nabila; Rachmat, Tia Destriana; Aeni, Ani Nur (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
Religious Education in elementary schools has a very important role in developing the character and morals of students since the beginning of human history. This research uses the Design and Development (D&D) method which aims to develop and test the effectiveness of a technology-based product. The product developed is a Google Sites-based digital site, "MEMANNAH", which presents the historical story of the Prophet Muhammad SAW in fostering the economy of Medina as a learning material for Grade 5 PAI at SDN Tanjungkerta. This research involves the stages of product design, development, implementation, and evaluation. Based on the results of research that has been conducted by researchers in grade 5 of Tanjungkerta Elementary School obtained from data processing based on the research instruments used. The results of the study include analysis of questionnaire data that has been given to students, as well as validation of material experts and media experts conducted to assess the feasibility and effectiveness of the digital site "MEMANNAH" as a learning media in Islamic religious education subjects. The digital site "MEMANNAH" effectively increases the motivation and effectiveness of student learning in understanding the teachings of the Prophet Muhammad SAW in building the economy of Medina. It can be seen from learners' acceptance of digital-based learning media, with 93.75% of students stating that this site helps them understand the material better.